The functioning of freshwater ecosystems - Le Cren, E.D. | Lowe-McConell, R.H (Estados Unidos | ESTADOS UNIDOS Cambridge University / New York, 1980)
Contents: History development of the freshwater production analyses based on models; Chemical budgets and nutrients pathways; Primary production; Segundary Production
Sin Especificar
Keywords: Ecología de agua dulce | Ecosistema-Agua dulce | Agua dulce-Productividad